2017
DOI: 10.1080/19315864.2017.1408724
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Enablers to Accessing Mental Health Services for People With Intellectual Disability: A Scoping Review

Abstract: Background: It is well established that people with an intellectual disability have high rates of mental health problems, yet rates of uptake of services do not match need. Aim:To identify the current literature pertaining to the barriers and facilitators to access to mental health services for people with an intellectual disability. Method: A systematic search identified English-language articles that addressed barriers or enablers to access, mental health services and intellectual disability from 2005 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
125
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(132 citation statements)
references
References 36 publications
5
125
1
1
Order By: Relevance
“…First, results revealed that individuals with ID‐only had significantly more frequent ED visits during adolescence than individuals in the PC group after controlling for sex, race/ethnicity, and insurance status. This finding speaks to the barriers to healthcare utilization faced by individuals with ID‐only, which include a lack of specially trained clinicians [Whittle, Fisher, Reppermund, Lenroot, & Trollor, ], difficulties navigating the healthcare system [Hanlon et al, ; Whittle et al, ], and communication barriers [Hanlon et al, ]. Interestingly, although those with ID‐only had significantly more ED visits during adolescence than the PC group, those with ASD + ID did not.…”
Section: Discussionmentioning
confidence: 99%
“…First, results revealed that individuals with ID‐only had significantly more frequent ED visits during adolescence than individuals in the PC group after controlling for sex, race/ethnicity, and insurance status. This finding speaks to the barriers to healthcare utilization faced by individuals with ID‐only, which include a lack of specially trained clinicians [Whittle, Fisher, Reppermund, Lenroot, & Trollor, ], difficulties navigating the healthcare system [Hanlon et al, ; Whittle et al, ], and communication barriers [Hanlon et al, ]. Interestingly, although those with ID‐only had significantly more ED visits during adolescence than the PC group, those with ASD + ID did not.…”
Section: Discussionmentioning
confidence: 99%
“…In provision of psychiatric services to people with intellectual disability, several factors result in patients and carers experiencing difficulty in attending out-patient appointments. 1 As intellectual disability services often cater for large geographical areas, these factors include inconvenient travel. 2 In the UK, there is an emphasis on finding efficiencies and providing cost reductions to address the political austerity agenda.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has become imperative to understand the health care needs of students with disabilities [26][27][28]. For instance, listening to students' experiences, their challenges and needs when accessing health services is an opportunity to examine their priorities and preferences in health service planning.…”
Section: Introductionmentioning
confidence: 99%